Cognitive behavioural therapy for insomnia - Aversa Lopes, Eliane (Cochrane Database Syst Rev, 2007)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To examine the effectiveness and safety of cognitive behavioural therapy for insomnia in adults aged 18 to 59 years.